The Relationship Between Body Mass Index and Blood Sugar with Cognitive Function in Patients with Diabetes Mellitus - Azahra Khansa Muza; Sulistyani Sulistyani; Siti Soekiswati; Iin Novita Nurhidayati Mahmuda (Universitas Muhammadiyah Purwokerto, 2023)
Impaired cognitive function is an individual's inability to perform daily functions and limits the quality of life. The prevalence of cognitive dysfunction in people in China, Spain, America, and Canada is 12.6%, 22.2%, and 16.8%. The prevalence of cognitive impairment that often occurs in Indonesia, namely dementia, is 10%. Insulin resistance causes inflammation and mitochondrial dysfunction. The state of hyperglycemia occurs activation of pro-inflammatory cytokines that cause cognitive impairment. This study aims to determine the relationship between body mass index and blood glucose on cognitive function in patients with diabetes mellitus at the Gatak Sukoharjo Health Center, consisting of 36 patients. Research using observational analytics with Pearson test. The sample selection technique is purposive sampling. Based on the results of the study with the Pearson test (p = 0.043), it means that there is a significant relationship. Furthermore, obtained (p = 0.578) means that there is no significant relationship. The conclusion of the study is that there is a relationship between body mass index and cognitive function, but there is no relationship between transient blood sugar and cognitive function in patients with diabetes mellitus.